2021
DOI: 10.1093/ofid/ofab466.638
|View full text |Cite
|
Sign up to set email alerts
|

439. Corowa-kun: Impact of a COVID-19 Vaccine Information Chatbot on Vaccine Hesitancy, Japan 2021

Abstract: Background Japan has one of the highest vaccine hesitancy rates in the world. According to a previous study, less than 30% of people strongly agreed that vaccines were safe, important, or effective. We created a COVID-19 vaccine information chatbot in a popular messenger app in Japan to answer COVID-19 vaccine frequently asked questions (FAQs) via text messages. We assessed the impact of chatbot text messages on COVID-19 vaccine hesitancy by conducting a cross-sectional survey among chatbot u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…A cross-sectional study (pre-print) found that a chatbot implemented via the most popular messenger app in Japan increased vaccination intentions. However, this was a low quality study with no control group and pre- and post-vaccine intentions were measured after the intervention [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…A cross-sectional study (pre-print) found that a chatbot implemented via the most popular messenger app in Japan increased vaccination intentions. However, this was a low quality study with no control group and pre- and post-vaccine intentions were measured after the intervention [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…For COVID-19 vaccination, our study lends weight to previous findings that interactive conversations between chatbots and users can contribute to increased vaccine confidence, as seen in the Thailand child group 27,52 . Additionally, since our chatbots were hosted on two major mobile messenger apps, WhatsApp and Facebook Messenger, our study also adds weight to previous evidence supporting the potential of mobile messenger applications in delivering vaccination knowledge, debunking vaccine-related misinformation, and providing vaccination guidance to unvaccinated individuals 53,54 . Our data showed that a majority of chatbot users were less likely to decrease in vaccine confidence and acceptance, compared with non-users; however, our study also found some apparent evidence of 'backfire' effects, specifically among some chatbot using parents in Hong Kong where we observed decreased vaccine acceptance with chatbot use.…”
Section: Discussionmentioning
confidence: 75%
“…Since guardians can make direct or indirect vaccination decision on behalf of children and seniors, we tested the effectiveness of chatbot in increasing guardians' vaccine confidence and acceptance for their dependent family members. Taking an average of estimates from similar studies conducted in Japan and France 53,68 , we estimated an effect size of 15% and determined a sample size of 250 for each of the control and intervention group using power analysis. However, our sample sizes did not reach the target due to the surge in vaccine uptake at the time of participant recruitment following the emergence of Omicron and subsequent governmental vaccine mandates, school-based vaccine rollouts and increased risk perceptions of COVID-19 (Supplementary Fig.…”
Section: Study Populationmentioning
confidence: 99%